A dispensa individual motivada sob a perspectiva constitucional - Dias, Maria Beatriz Ribeiro (2013)
The labor is a factor of production that, besides supporting the economy, provides to Human Beings means to guarantee their livelihood and their basic needs. Therefore, it is valued by the Constitution of the Federative Republic of Brazil as the foundation of the Federal Republic, as a principle of the economic order, and as the basis of the social order. In this sense, mechanisms for employment protection acquire importance. The object of this study is the analysis of the individual motivated dismissal from the perspective of Article 7, I, of the Constitution of the Federative Republic of Brazil. We sought to identify its classification and consequences of its application, based on the historical analysis, on the international standard, and on the Portugal's law, which is a country with culture, social and economic influence similar to Brazil, and with an interesting proceeding for the individual motivated dismissal. With regard to the research techniques, we use both documental and bibliographical researches. In the bibliographical research we note the excellence of the authors chosen and the corresponding pertinence of the central theme of this dissertation, without excluding books that helped us to base concepts to complete this debate